(untitled) (Experimental biology, 2016)
We searched 239 miRNAs binding sites in mRNAs of 63 from 157 transcription factors genes of Camelus ferus Zinc finger family. 19 binding sites are located in the 5’UTRs, 64 sites are located in the CDSs and 156 sites are located in the 3’UTRs. The mRNA of GLI2 gene has binding sites for eight miRNAs. The ΔG/ΔGm value changed from 90 to 100 %. miR-1322 has one binding site in GLI1, HINFP, HIVEP1, MTF1, SALL4, SP1, ZNF335 and ZNF451 genes, two sites in ZNF142, three sites in EGR1 gene. The ΔG value varied from -114,6 kJ/mole to -138,0 kJ/mole. Some miRNAs with a length of 23 and 24 nucleotides also have a high value ΔG varied from -112,5 kJ/mole to -129,5 kJ/mole. The results show a strong interaction between the expression of genes of transcription factors and miRNAs.